2020
DOI: 10.1002/bjs5.50348
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein : albumin ratio in patients with resectable intrahepatic cholangiocarcinoma

Abstract: Background: The C-reactive protein : albumin ratio (CAR) has been reported as a novel prognostic marker in several cancers. The aim of this study was to investigate the prognostic value of CAR in patients with intrahepatic cholangiocarcinoma (ICC). Methods: This was a single-centre retrospective study of patients who underwent surgery for ICC in a university hospital in Japan between 1998 and 2018. CAR, Glasgow Prognostic Score (GPS) and modified GPS (mGPS) were calculated. Their correlation with recurrence-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…34 Several studies for predicting survival of ICC patients after surgery had been reported before. 36,37 Compared with these studies, our study has several advantages. Firstly, as a study based on multiple cohorts, the number of included patients in this study was larger than those of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…34 Several studies for predicting survival of ICC patients after surgery had been reported before. 36,37 Compared with these studies, our study has several advantages. Firstly, as a study based on multiple cohorts, the number of included patients in this study was larger than those of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since Fairclough et al. [43] first proposed CAR as a prognostic marker to identify acutely sick patients, multiple studies have demonstrated its predictive value regarding morbidity and mortality in critically ill patients [19,20,22,29], in cirrhotic patients awaiting liver transplantation [23,24], as well as in patients undergoing colorectal [21,30], pancreatic [25], gastro‐oesophageal [44,45] and liver [26,46] surgery. In oncological patients, an association has been shown between high CAR and lower overall‐ [44,47,48] and disease‐free survival rates [26,29], as well as advanced tumour stage [25,26,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an intrinsic limitation of CAR is its lack of specificity, as CRP and Alb levels are affected by a multitude of factors, as previously mentioned. Both CRP and Alb are synthesized in the liver [26,28,46,48], which explains their inclusion in clinical scores such as SOFT [7] and Child‐Pugh [54], which are used to stratify risk of adverse outcomes in patients with liver disease. Although the exact relationship between serum levels of CRP / Alb and liver dysfunction is a matter of dispute [20,28], it stands to reason, that patients with liver dysfunction may exhibit more distorted preoperative CAR, making comparisons with other patient cohorts undergoing surgery difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FIB, carbohydrate antigen 125 (CA125), LDH and iron. ALB has been used frequently as a prognostic indicator of ICC, for its relation with liver reserve function and nutritional status 22,23. FIB was also reported as a prognostic factor of CCA 24.…”
mentioning
confidence: 99%